جريمة التحريض الالكتروني - -مــــبــرك أيــــــــــــوب (المسيلة, 2022)
This spread and continuous development in information and communication technology was accompanied by the emergence of networks, electronic media and many means of social communication, and spread among student and youth circles. Electronic incitement destroyed and dismantled secure societies, as is the case in the Arab model called the Arab Spring revolutions such as Syria, Yemen and Libya. Algeria, too, has witnessed a series of security disturbances in its cyberspace, such as incitement to assault people and the call for civil disobedience, and the call for the overthrow of the regime, which prompted the state to raise the degree of security preparedness against this incitement in its electronic version that affects people and the system of government in the state by setting up a system Legal in line with urgent developments on the international and national arena, the aim of this study is to shed light on this type of crime in terms of criminalization and punishment.
Keywords: جريمة -التحريض الالكتروني